Exploration of the SIRT1-mediated BDNF–TrkB signaling pathway in the mechanism of brain damage and learning and memory effects of fluorosis - Wang, Feiqing; Li, Yanju; Tang, Dongxin; Yang, Bo; Tian, Tingting; Tian, Mengxian; Meng, Na; Xie, Wei; Zhang, Chike; He, Zhixu; Zhu, Xiaodong; Ming, Dong; et al. (Frontiers in Public Health, 2023)
Introduction Fluoride is considered an environmental pollutant that seriously affects organisms and ecosystems, and its harmfulness is a perpetual public health concern. The toxic effects of fluoride include organelle damage, oxidative stress, cell cycle destruction, inflammatory factor secretion, apoptosis induction, and synaptic nerve transmission destruction. To reveal the mechanism of fluorosis-induced brain damage, we analyzed the molecular mechanism and learning and memory function of the SIRT1-mediated BDNF–TrkB signaling pathway cascade reaction in fluorosis-induced brain damage through in vivo experiments. Methods This study constructed rat models of drinking water fluorosis using 50 mg/L, 100 mg/L, and 150 mg/L fluoride, and observed the occurrence of dental fluorosis in the rats. Subsequently, we measured the fluoride content in rat blood, urine, and bones, and measured the rat learning and memory abilities. Furthermore, oxidative stress products, inflammatory factor levels, and acetylcholinesterase (AchE) and choline acetyltransferase (ChAT) activity were detected. The pathological structural changes to the rat bones and brain tissue were observed. The SIRT1, BDNF, TrkB, and apoptotic protein levels were determined using western blotting. Results All rats in the fluoride exposure groups exhibited dental fluorosis; decreased learning and memory abilities; and higher urinary fluoride, bone fluoride, blood fluoride, oxidative stress product, and inflammatory factor levels compared to the control group. The fluoride-exposed rat brain tissue had abnormal AchE and ChAT activity, sparsely arranged hippocampal neurons, blurred cell boundaries, significantly fewer astrocytes, and swollen cells. Furthermore, the nucleoli were absent from the fluoride-exposed rat brain tissue, which also contained folded neuron membranes, deformed mitochondria, absent cristae, vacuole formation, and pyknotic and hyperchromatic chromatin. The fluoride exposure groups had lower SIRT1, BDNF, and TrkB protein levels and higher apoptotic protein levels than the control group, which were closely related to the fluoride dose. The findings demonstrated that excessive fluoride caused brain damage and affected learning and memory abilities. Discussion Currently, there is no effective treatment method for the tissue damage caused by fluorosis. Therefore, the effective method for preventing and treating fluorosis damage is to control fluoride intake.